Analisis Metode Penetapan Harga Jual Roti dalam Meningkatkan Penjualan pada Pabrik Roti Karunia Mandiri Kendari - Ringan, Angelina Yenny; Dahlan, Jamaluddin (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the method of determining the selling price of bread against sales at the Karunia Mandiri Bread Factory in Kendari. This study is a descriptive qualitative study. The data used are primary and secondary data obtained in the form of documents sourced from the Karunia Mandiri Bread Factory. Data collection techniques use documentation techniques, observation techniques and interview techniques using variable costing techniques through the calculation of raw material costs, labor costs and factory overhead costs. The results of this study indicate that the cost of raw materials used often encounter obstacles, labor costs are costs that have been patented by the Karunia Mandiri Bread Factory in accordance with the UMR, unexpected costs for electricity and telephone credit costs provided. Several types of costs used in determining selling prices are influenced by market selling prices so that the price determination is adjusted to the increase or decrease in costs incurred and the size of the bread in production each month. Pricing is adjusted to the cost of basic materials and labor costs incurred.